Alt solunum yolu enfeksiyonu tanısı almış çocuklarda, ebeveynlere verilen eğitimin aile memnuniyetine etkisi - Yıldırım, Zeynem (My University, 2013)
Bu araştırma, 0-5 yaş arası alt solunum yolu enfeksiyonu tanısı almış çocukların ebeveynlerine verilen eğitimin, memnuniyet düzeylerine etkisini ve tekrar hastaneye yatışı değerlendirmek amacıyla yarı deneysel olarak gerçekleştirilmiştir. Araştırmanın örneklem grubunu Tekirdağ Devlet Hastanesi Çocuk Hastalıkları Kliniği’ne 15 Mart – 15 Mayıs 2013 tarihleri arasında alt solunum yolu enfeksiyonu tanısı ile yatmış 0-5 yaş arası çocuklar (30 deney, 30 kontrol) oluşturmuştur. Veri toplama araçları olarak; sosyodemografik bilgiler için “Çocuk ve Aileyi Değerlendirme Formu”, çocuğun solunum fonksiyonlarını değerlendirmek için “Solunum Sistemi Fizik Muayene Formu”, memnuniyeti değerlendirmek amacıyla “PedsQL Sağlık Bakımın Memnuniyet Ölçeği” ve 3 ay içerisinde hastaneye tekrar yatışı değerlendirmek için “Takip Formu” kullanılmıştır. Araştırmacı tarafından hazırlanan, “Alt Solunum Yolu Enfeksiyonu Tanısı Almış Çocukların Bakım Kitapçığı” ile deney grubu ebeveynlere eğitim verilmiştir. Verilerin karşılaştırılmasında iki grup arasındaki farkı t-testi, grup içi tekrarlı ölçümlerin karşılaştırılmasında eşleşmiş grup t-testi kullanılmıştır. Araştırmada, eğitim alan deney grubu ebeveynlerin memnuniyet puan ortalamaları kontrol gruba göre istatiksel olarak anlamlı düzeyde yüksek bulunmuştur. 3 aylık izlem sonucunda her iki grupta da yer alan çocukların tekrar hastaneye yatış oranlarında anlamlı farklılık saptanmamıştır. Sonuç olarak; alt solunum yolu enfeksiyonu tanısı almış çocukların ebeveynlerine verilen eğitimin, ebeveyn memnuniyetini arttırdığı görülmüştür. Anahtar Kelime: Solunum yolu enfeksiyonu, hemşirelik, ebeveyn memnuniyeti, eğitim

THE AFFECT OF EDUCATION, PROVIDED TO THE PARENTS OF CHILDREN DIAGNOSED AS LOWER RESPIRATORY TRACT INFECTIONS, ON FAMILY SATISFACTION. This study has been conducted as quasi-experimental in order to assess the education, which has been provided to the parents of children, between the ages of 0-5, and diagnosed as lower respiratory tract infections, in terms of parents’ satisfaction level and children’s readmission to the hospital. The research universe consists of the children, diagnosed as lower respiratory tract infections and hospitalized at Public Hospital, Pediatri Clinic in 2012 in Tekirdağ. The sample of the study however, consists of 60 parents (30 for study and 30 for control groups) who were chosen using “ random sampling method”, between the dates of 15th March and 15th May, 2013. The necessary data were obtained from the literature. “Child and Parent Assessment Form” was used for socio-demographic data and “Physical Examination Form for Respiratory Tract” was used to assess the function of respiratory tract. Furthermore, “PedsQL Health Care Satisfaction Form” was used to evaluate the satisfaction level and “Follow-up Form” was applied for the assessment of readmission to the hospital within 3 months. In addition; study group parents were provided education with the help of the hand book which is about the “caring of the children diagnosed as lower respiratiory tract infections” prepaired by the researcher. The data obtained from the study were analyzed through computor environment.It was identified that variables showed a normal disribution. As for comparing the data; T-test was applied in order to find out the differences between two groups and “Matching group T-test” was applied to compare the repeated measurements within the group. According to results; when the gender of the children, no matter in which group they belong, their parents’ education status, their having an illness, were compared not any significant differences occured between two groups and an homogeneous distribution was obtained as well. The mean scores of parents, to whom some education was provided, were higher than the rest of them and also, a significant difference was detected between the ones who got education and who did not get any education. It was also put forth that the effective education, provided to the parents of children with lower respiratory tract infections, increase the level of parents’ satisfaction. Key Words: Respiratory tract infections, nursing, parents’ satisfaction, education.
Keywords: Çocuk Hastalıkları Hemşireliği; Çocuk Sağlığı Hizmetleri; Solunum Yetmezliği